Melodrama, subjectivity and recognition in television fiction. Proposal for an approach María Victoria Bourdieu - Bourdieu, María Victoria (2020)
We propose to briefly state the concepts that relate the melodrama to a way of being and to be in Latin America, how mass media -especially television- have adopted it and adapted it to constitute it in “the way” of narrating ourselves. We will provide a way to approach to fictional content in television that allows us to read the subjectivities and particular recognitions, always in tension with other fictions of diverse origins, whose productions have strong contributions of capital, talent, and expertise. This invitation, in short, is nothing more than a reflection that attempts to unravel the idea that there is “a large” global village of which we are part of undividedly, as opposed to the idea that, despite the great penetration of audiovisual productions from different latitudes, there are territorial identifications that contribute to this collective construction of Latin American identity, whose best form of understanding is rooted in the melodramatic.